Motor Evoked Potentials in Hereditary Spastic Paraplegia—A Systematic Review - Siow, Sue-Faye; Cameron Smail, Ruaridh; Ng, Karl; Kumar, Kishore R.; Sue, Carolyn M. (Frontiers in Neurology, 2019)
Background:Hereditary Spastic Paraplegia(HSP) is a slowly progressive neurodegenerative disorder with no disease modifying treatment. Potential therapeutic approaches are emerging and large-scale clinical drug trials for patients with HSP are imminent. A sensitive biomarker to measure the drug efficacy in these trials is required. Motor evoked potentials (MEPs) are a potential biomarker for HSP as they assess the central motor pathways and can be standardised with set protocols and guidelines. Objectives:We performed a systematic review to investigate the utility of MEPs as a diagnostic and disease severity biomarker for HSP. Search Methods:Systematic searches of PubMed, Embase, Medline and Scopus were performed. Selection Criteria:Studies reporting on central motor conduction time measured with MEPs in adult and paediatric patients with HSP were included. We excluded studies in non-HSP patient cohorts, not in English, not original research and unpublished journal articles. Data Collection and analysis:Search results were de-duplicated and screened according to the inclusion and exclusion criteria. The included papers were reviewed independently by two reviewers and data was collected on patient cohorts, test methods, results and study quality. Results:Of the 882 search results, 32 studies were included in the review. The most common finding was absent or prolonged lower limb(LL) CMCT in patients with HSP(78% of patients studied). Quality assessment revealed variability in study methodology and reporting of results. Variations included patient cohorts of various genotypes as well as variations in equipment and techniques used. Aside from CMCT, none of the MEP parameter measures correlated with disease severity and many did not show significant difference between HSP patients and controls. Conclusion:Systematic review of MEP studies in HSP patient cohorts demonstrated mixed findings. LL CMCT was the most promising parameter in terms of differentiating HSP patients from controls, with one study demonstrating a weak correlation with clinical disease severity. It is possible that the variability in study methodologies and small patient cohorts have contributed to the variable findings. A longitudinal study of MEP in a large cohort of HSP patients with the same genotype will help clarify the utility of MEPs as a biomarker for disease severity and use in clinical trials.